Produksi Perangkat Penepat Mata Bor Diameter 12 mm pada Pengasahan Gerinda Manual, Kapasitas 0,125 Unit/Jam - Wirahadi Yudha Juanda; Syamsul Hadi; Alexander Theo Saputra; Fahmi Idris; Abel Chelsea Pratama (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2026)
Sharpening steel drill bits using a manual grinding machine often results in an incorrect angle that affects machining performance as a problem encountered. The production objective is to obtain a jig for grinding bit movement on the abrasion surface of the drill bit tip with a diameter between 6 mm and 16 mm until sharp. The production method includes: design of a jig with a feed thickness adjustment device from 0.1 mm to 0.3 mm, a movement angle adjustment from 0o to 33o, and a radius movement adjustment from 30 mm to 40 mm; selection of jig materials; 3D printing of ABS material for a jig for sharpening the cutting edge of the drill bit; testing of a jig for sharpening the cutting edge of the drill bit; performance analysis; and inspection of product quality and dimensions. The production results are in the form of a manual grinder for sharpening drill bits with a diameter between 6 mm and 16 mm with a total production cost of IDR 230,000/unit, and a process duration of 8 hours/unit, which implies that sharpening the blunt end of drill bits with a diameter between 6 mm and 16 mm can be carried out more quickly than manually.